Impact of long-term resource variations on wave energy Farms: The Icelandic case. (1st February 2020) - Penalba, Markel; Ulazia, Alain; Saénz, Jon; Ringwood, John V.
Abstract: Four decades (between 1979 and 2018) of the wave energy resource around Iceland are analysed in the present paper via the ERA5 reanalysis, the newest reanalysis of the European Centre for Medium-Range Weather Forecasts . While the overall long-term wave trend observed is unremarkable, particularly between the last two decades, in the northern area, near Greenland, a substantial increase of the wave energy resource is detected. In addition, an exceptional decade (between 1989 and 1998) with an extraordinarily high wave energy resource (increasing over 15% with respect to the previous decade) is observed, which emerges due to high values of the indices corresponding to teleconnection patterns, such as the Arctic Oscillation or the East Atlantic pattern. This increase of the total wave energy resource results in more frequent extreme events (up to 35% of the total resource) and, as a consequence, the exploitable wave energy (excluding these extreme events) does not increase proportionally. However, a substantial impact on WEC average power generation is observed, with over 500 kW of difference between two subsequent decades in a WEC farm of 45 devices, meaning that the analysis of long-term resource variations is crucial for an accurate design of different components in the WEC farm. Highlights: No relevant overall wave trend is found in Iceland. However, a significant positive wave trend (up to 8.9 kW/m per decade) is found in the northern area. Substantial decadal variations are observed due to teleconnection patterns. The impact of these teleconnection patterns in the performance of wave energy converters is significant.